2009
DOI: 10.1212/wnl.0b013e3181a2e846
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared spectroscopy in carotid artery stenting predicts cerebral hyperperfusion syndrome

Abstract: Periprocedural increases in regional cerebral oxygen saturation measured by near- infrared spectroscopy can be an excellent predictor of cerebral hyperperfusion syndrome after carotid artery stenting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 30 publications
2
30
1
Order By: Relevance
“…The rSO 2 was slightly higher than on the opposite side immediately after recanalization because of reperfusion of the occluded carotid artery. Post-stenting hyperperfusion syndrome is reported to occur frequently if the rSO 2 is 10% or more higher than the baseline value 3 minutes after recanalization, 5) but the increase was less than 10% in both our patients, and hyperperfusion syndrome was not observed in either patient.…”
Section: Disclosure Statementcontrasting
confidence: 54%
“…The rSO 2 was slightly higher than on the opposite side immediately after recanalization because of reperfusion of the occluded carotid artery. Post-stenting hyperperfusion syndrome is reported to occur frequently if the rSO 2 is 10% or more higher than the baseline value 3 minutes after recanalization, 5) but the increase was less than 10% in both our patients, and hyperperfusion syndrome was not observed in either patient.…”
Section: Disclosure Statementcontrasting
confidence: 54%
“…Thus, the efficacy of NIRS, which was the second most common modality used to detect the hyperperfusion phenomenon in this study, may be promising. 27) The low penetration rate of TCD (<10%) in this study was thought to reflect the fact that most of the Japanese neurointerventionalists were neurosurgeons 8) and that insonation through the temporal bone window was limited in elderly Asian (Japanese) people. 28) There were two institutes that performed the X-ray angiography perfusion analysis using the application that was bundled with their angiography equipment.…”
Section: Resultsmentioning
confidence: 82%
“…Ogasawara et al [15] reported that HP can be detected immediately after carotid endarterectomy by SPECT, and Matsumoto et al [18] reported that the increase in CBF detected just after CAS using near-infrared spectroscopy predicts the cerebral HP syndrome. HP starts during carotid artery stenosis surgery, and we detected dynamic IC dilation due to an increase in blood flow that can induce the HP syndrome.…”
Section: Discussionmentioning
confidence: 99%